MODEL PEMBELAJARAN KONTEKSTUAL DALAM PEMBINAAN AKHLAK SISWA DI MAN 2 MODEL MEDAN - Hirawti Hirawati (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: Contextual learning model is a learning concept that helps students to the formation ofcritical, active and innovative attitude, because the students have the opportunity to try it by theirown experience and construct it through the guidance and direction of the teacher. The learningprocess takes place naturally in the form of student activities learn and experience it. Implementationof Contextual Learning Model in the Development of Student Morals in Madrasah Aliyah Negeri 2Medan Model aims to make learning more productive and meaningful. This thesis includes the typeof qualitative research. The study intends to understand what subjects are experiencing. In this studydata collection using observation, interviews, and documentation. The collected data is then analyzedusing descriptive analysis method. Further data processing using three main steps in research,namely: data reduction, data presentation (display data), and verification (inferring data). In thisresearch, it turns out the contextual learning model in the learning process becomes better than theconventional learning model. Learning becomes more actively creative and innovative. In addition toteachers convey the material and integrate the moral values by inviting students to accustomed toapply the moral values in everyday life, teachers also managed to bring up some components ofcontextual learning on the learning model, among others:1) constructivism arises because the experiencegained by finding students by themselves; 2) finds (inquiry) appear on assignment and poursthe observations and draws conclusions; 3) questions (questionsing) arise when students ask aboutassigned problems, discussions, work in groups when answering questions of direction; 4) Learningcommunity emerged during group discussions and class discussions; 5). Modeling occurs when theteacher gives an example.